Examining the Motor Phenotype of Patients with Both Essential Tremor and Parkinson's Disease. (21st May 2012) - Simões, Rita M.; Constantino, Anne; Gibadullina, Eliza; Houghton, David; Louis, Elan D.; Litvan, Irene
Background: The subset of patients with essential tremor (ET) that develops Parkinson's disease (PD) has not been fully clinically characterized. Methods: Motor features were retrospectively reviewed in 18 ET patients who developed PD (ET→PD), 20 ET and 30 PD patients with similar ages and disease durations. Results: Fewer ET→PD than ET patients had widespread postural and/or action tremor (2/17 [11.8%] vs. 11/17 [64.7%]; p = 0.001) and marginally fewer had cerebellar signs (1/15 [6.7%] vs. 6/18 [33.3%], p = 0.06). ET→PD patients required fewer ET medications than did their counterparts with ET (p = 0.001). ET→PD patients and PD patients did not differ in UPDRS, Hoehn and Yahr, or Schwab and England scores (each p≥0.14). Discussion: ET patients who develop PD may have distinct pre-PD motor features compared to their counterparts with ET who do not develop co-existing PD. Prospective studies are needed to evaluate the predictive value of these clinical features for the emergence of PD.